CT and MRI Appearances of Primary Sphenoid Melanoma: A Rare Case - Batra, Kiran (AJNR Am J Neuroradiol, 2005)
Summary: Primary sphenoid melanoma is a rare tumor. A 75-year-old man presented with complaints of headache and visual complaints for a few days. CT and MRI of the brain demonstrated a sphenoid sinus mass with appearances suggesting a diagnosis of melanoma. Fine-needle aspiration biopsy confirmed the diagnosis. Other differential diagnostic considerations on CT and MRI are discussed. We also discuss the further role of contrast MRI in determining the actual extent of the tumor in the critical skull base area.